Very simple method of concentration of iron-free quartz-diopside ores from Slyudyansk deposits; Glass and Ceramics; Vol. 51, N 5-6 - Alekseev Yu. I.; Reznitskii L. Z.; Vereshchagin (Vereschagin, Vereshagin) V. I. Vladimir Ivanovich; Vasil'ev E. P.; Vakalova T. V. Tatyana Viktorovna (1994, 1994)
В фонде НТБ ТПУ отсутствует